A Survey of the Management of Neuromuscular Blockade Monitoring in Australia and New Zealand. Issue 3 (May 2013) - Phillips, S.; Slewarl, P. A.; Bilgin, A. B.
This survey of anaesthetists in Australia and New Zealand aimed to investigate their attitudes and practice relating to the management of neuromuscular blockade monitoring. All medical practitioner members (3188) of the Australian and New Zealand Societies of Anaesthetists were invited to complete an anonymous survey, which was available online for two months. A total of 678 survey questionnaires were completed (response rate 21%). Most respondents (71.4%) underestimated the incidence of residual neuromuscular blockade and 63.2% believed this to be a significant clinical problem. Objective monitoring of neuromuscular function was used routinely only by 17% of respondents, although 70% believed routine monitoring would reduce the incidence of residual neuromuscular blockade. Only 25% of respondents correctly indicated that quantitative train-of-four counts of greater than 90% were the accepted criteria for safe extubation, with 52% using clinical judgement only. Only 29% of respondents believed neuromuscular function monitors should be part of minimum monitoring standards; quantitative neuromuscular function monitors were not available in 42% of the hospitals in which the respondents practiced. Despite the low response rate, the large sample size and heterogeneity of respondents make the findings of this survey concerning. There is a need for more education, availability of appropriate monitoring equipment and evidence-based guidelines for management of neuromuscular blockade in Australia and New Zealand.